Design and Fabrication of Batio3 Humidity Sensor Using Thick Film Screen Printing Technique - Wan Zaki, Wan Suhaimizan (2006)
Thick film sensor technology has been recognized as an important technology in sensor manufacturing for the last decade. The technology contributes to the sensor development with the exploitation of the film itself as a primary sensing device. Most ceramic materials have been investigated as a humidity sensor mainly on porous structure prepared by thick film technology. These films have microstructure properties similar to those of sintered porous bodies, but the dimensions of the sensing devices can be reduced, which then can be used in hybrid circuits.